Transpsoas Lumbar Interbody Fusion Without Psoas Stimulated Electromyography. Issue 1 (February 2021) - Patel, Shyam A.; Goyal, Dhruv K.C.; Reid, Daniel; Patel, Ram; Babu, Jacob; Fereydonyan, Naderafshar; Anderson, David Greg
Abstract : Study Design: This is a retrospective case review. Objective: The objective of this study was to present an anatomic approach to transpsoas interbody fusion without psoas stimulated electromyography (sEMG) and to evaluate the rate of neurological and approach-related complications. Background: The transpsoas approaches have become commonly utilized for lumbar interbody fusion and may have certain advantages compared with other methods of interbody stabilization. Traditionally, transpsoas approaches have been performed utilizing sEMG as it has been purported to reduce the risk of injury to the lumbar plexus; however, an anatomic approach to transpsoas surgery is also possible as cadaveric studies have demonstrated the anatomy of the psoas muscle and lumbar plexus. Methods: Patients who underwent transpsoas interbody fusion using an anatomic approach without psoas sEMG between 2005 and 2018 were enrolled in this study. The preoperative and postoperative medical records for this cohort were carefully reviewed to identify any new or persistent radicular symptoms, neurological deficits or approach-related complications. Results: A total of 133 patients (48 males, 85 females) underwent transpsoas interbody fusion at 222 levels in this cohort—which had a mean age of 63 (61, 65) years and body mass index of 28.8 (27.8, 29.9). New neurological complications were seen in 5 patients (3.8%) and 5 patients (3.8%) were found to have new postoperative radicular pain, up to 3 months postoperatively. The total number of perioperative, approach-related complications was 7 (5.3%) for the entire cohort. Conclusion: An anatomic transpsoas approach to the interbody space without psoas sEMG demonstrated a rate of neurological and approach-related complications that was comparable or superior to the rate of complications reported using the traditional transpsoas approach with sEMG.